Physicochemical and microbiological analysis of drinking water treated by using ozone - Subedi, D.P; Tyata, R.B; Khadgi, A; Wong, C.S (Universiti Kebangsaan Malaysia, 2012)
This study focused on the application of a Dielectric Barrier Discharge (DBD ) unit to produce highly oxidizing ozone molecules for the treatment of drinking water. The samples of water were collected from three different sources, namely tap, stone spout and tube-well in the Kathmandu valley. Various physical, chemical and micro-biological analyses were carried out to both the ozone treated and untreated samples of water for comparison. Our results indicated that ozone does not alter the physical characteristics, namely pH, conductivity and turbidity of water but it has significant effect on the chemical properties such as nitrate concentration, total hardness, calcium hardness, Fe(II) and Fe(III) concentration. It was observed that ozone efficiently precipitates ferrous ion into ferric ion and is effective in the removal of fecal coliform, a key element for various water related health problems in most of the developing countries. It is shown that the treatment with ozone leads to a significant reduction in the number of fecal coliform in the samples of drinking water from tap, stone spout and tube well with p values 0.00182, 0.026 and 5.8 ×10-15, respectively at 0.05 level of significance.